The Influence Of Return On Asset, Debt To Equity Ratio, Earnings Per Share On Stock Prices With Dividend Policy As A Moderation Variable In Banking Companies Listed On The Indonesian Stock Exchange Period 2018-2022 - Nia Nur Aini; Dwi Soegiarto; Tina Rahayu (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
This study aims to analyze the effect of return on assets, debt to equity ratio, earning per share on stock prices with dividend policy as a moderating variable. The population of this study were 47 companies. The sampling process using purposive sampling method amounted to 12 companies in a 5-year period, so the total sample was 60. The data analysis method used in this study is descriptive statistical analysis, classical assumption test and hypothesis testing with the help of SPSS version 25 software: 1) return on assets has a positive and significant effect on stock prices, 2) debt to equity ratio and earning per share have a negative and significant effect on stock prices, 3) Dividend policy is able to moderate the relationship between return on assets on stock prices, 4) Dividend policy is able to moderate the relationship between debt to equity ratio on stock prices, 5) Dividend policy is able to moderate the relationship between earning per share on stock prices.